Magnocellular training improves visual word recognition - Chouake, Tara; Levy, Tamar; Javitt, Daniel C.; Lavidor, Michal (Frontiers in Human Neuroscience, 2012)
Current research has shown that basic visual networks, such as the magnocellular system, may play a crucial role in reading deficits related to dyslexia. The current study explored the relationship between magnocellular activity and reading abilities; we examined the hypothesis that a repeated usage of the magnocellular stream may improve reading by strengthening crucial neural pathways. Visual training was conducted for five consecutive days using a motion detection task (magnocellular training) and a control task of pattern detection (parvocellular training). Reading abilities of skilled readers were measured before and after the training using a lexical decision task. It was found that low-grade visual training overall can improve speed of lexical decision, but there is some indication that magnocellular training may selectively relate to accuracy. This potential added benefit of accuracy is crucial, and indicates that magnocellular training may have an advantage to parvocellular or general visual training when it comes to reading. This result lends support to the role of basic visual systems in reading, and has potential implications for neurorehabilitation of reading-related deficits.